2012
DOI: 10.1089/cap.2011.0056
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Pilot Trial of Mecamylamine for Treatment of Autism Spectrum Disorders

Abstract: Objective: To explore possible benefits of a nicotinic acetylcholine receptor (nAChR) agent for autistic symptoms based on postmortem observation of nAChR abnormalities (deficient a4b2 nAChRs, excess a7 nAChRs) in brains of patients with autism. Method: Mecamylamine, because of its safety record in children with other disorders, was chosen for this first exploration. Twenty children with autism spectrum disorder age 4-12 years were randomly assigned for 14 weeks to placebo (n = 8) or mecamylamine (n = 12) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 43 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…Twenty-five of these used ABC-I to assess IA. Eleven of the 25 studies targeted irritability (baseline ABC-I ≥18 or ABC-I specified as primary endpoint) as the main outcome measure and were included in the metaanalysis for therapeutic effects of medications on IA ( 28 citalopram, 29 clonidine, 30 dextromethorphan, 31 levetiracetam, 32 mecamylamine, 33 naltrexone, 34,35 omega-3 fatty acid, 36 secretin, 37 tianeptine, 38 and venlafaxine 39 ; Supplemental Table 2); 5 studies did not report baseline ABC-I (clonidine, dextromethorphan, levetiracetam, naltrexone, and venlafaxine). The 10 RCTs that did not use ABC-I to assess IA (Supplemental Table 3) represented 8 placebo-controlled trials and 2 head-to-head trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five of these used ABC-I to assess IA. Eleven of the 25 studies targeted irritability (baseline ABC-I ≥18 or ABC-I specified as primary endpoint) as the main outcome measure and were included in the metaanalysis for therapeutic effects of medications on IA ( 28 citalopram, 29 clonidine, 30 dextromethorphan, 31 levetiracetam, 32 mecamylamine, 33 naltrexone, 34,35 omega-3 fatty acid, 36 secretin, 37 tianeptine, 38 and venlafaxine 39 ; Supplemental Table 2); 5 studies did not report baseline ABC-I (clonidine, dextromethorphan, levetiracetam, naltrexone, and venlafaxine). The 10 RCTs that did not use ABC-I to assess IA (Supplemental Table 3) represented 8 placebo-controlled trials and 2 head-to-head trials.…”
Section: Resultsmentioning
confidence: 99%
“…32 Mecamylamine, a nicotinic acetylcholine receptor antagonist used for treating hypertension, failed to show an effect in treating IA in ASD. 33 Amantadine, a dopaminergic agent used for treating Parkinson's disease, was also indistinguishable from placebo. 40 Omega-3 fatty acid 36 (antioxidant) and secretin 37 (endogenous hormone regulating secretions from the stomach and pancreas) also showed no significant advantage over placebo.…”
Section: Figurementioning
confidence: 99%
“…This was based primarily on the low prevalence of smoking in the ASD population [124, 125], although this may due to the loss of expression of the α4β2 * nAChRs early in development and presumably loss of sensitivity to the rewarding properties of nicotine since the α4β2 * receptors are primarily responsible for the addictive properties of nicotine [126, 127]. In support of this notion, in a placebo-controlled pilot study with a nonselective and noncompetitive antagonist of the nAChRs, mecamylamine, it was found that while this drug was well tolerated, it lacked efficacy in treating autistic symptoms [128]. …”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…Few clinical trials have been designed to explore nicotinic agents for the specific management of agitation, irritability, and aggression specifically; however, evidence supporting a significant but complex role of nicotine and nicotinic receptors in these syndromes can be gleaned from a variety of clinical studies with different primary outcomes that also report on these data (Arnold et al, 2012; Conners et al, 1996; Drusch et al, 2013; Newhouse et al, 1994), as well as well-conducted case series (Mayer et al, 2001; Rosin et al, 2001). A second line of evidence comes from a number of studies describing the prominence of ARBS in the context of nicotine withdrawal (Lucidarme et al, 2010), and the tendency for these symptoms to resolve following administration of nicotine (Schechter, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual overlap between ‘sudden mood changes’ and ARBS is intuitive, although not definitive, and further work would be required to confirm the nature of this effect. Even more preliminary findings come from a trial of mecamylamine in autism (Arnold et al, 2012). This small study reported no clinically or statistically significant benefit, but provided anecdotal evidence of decreased irritability in four cases.…”
Section: Introductionmentioning
confidence: 99%